Advanced Accounting/Advanced Accounting Problems (Book). - Cannon, Arthur M.; Newcomer, Hale L. (The Accounting Review, 1951)
Reviews two books. "Advanced Accounting," vol. 2, and "Advanced Accounting Problems," by George Hillis Newlove and S. Paul Garner.